Microclimate and heat unit requirement of maize (Zea mays L.) under different thermal environments, mulching and irrigation levels - Rani, Radha; Singh, Som Pal; Kingra, P K (Annals of Agricultural Research, 2017)
An experiment was conducted at the research farm of School of Climate Change and AgriculturalMeteorology, PAU, Ludhiana to study the effect of two dates of sowing (D1: 1st August and D2: 15thAugust), mulching (Mo: no mulch and M1: straw mulch @6 t ha–1) and three irrigation levels (IW:CPE= 0.50, 0.75 and 1.00) on microclimate and heat unit requirement of maize during kharif 2010.Photosynthetically active radiation (PAR) interception and relative humidity were higher in earliersown mulch applied crop under IW:CPE = 0.75 level of irrigation. Daytime soil temperature wasobserved to be lower under mulch application as compared to no mulch, however night timetemperature was slightly higher under mulch application. The data indicates that crop durationwas lengthened and higher degree days were consumed in the earlier sown mulch applied cropunder irrigation of IW:CPE = 0.75. Crop sown on 1st August irrigated at IW:CPE of 0.75 with mulchapplication @ 6.0 t ha–1 had most favourable microclimate supporting the yield parameters. Growingdegree days depicted positive and linear relationship with maize yield (R2 = 0.79) and harvest index(R2 = 0.62). Such microclimatic modifications can be highly beneficial for alleviation of heat andwater stress under changing climate and water limiting scenarios in future.